2018
DOI: 10.4236/psych.2018.94045
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Inclusive Leadership on Employees’ Procrastination

Abstract: Based on self-determination theory, our study investigates the mechanism and boundary condition of procrastination behavior. We had a sample of 327 employees to test our hypothesis, and regression method and the structural equation model were used to analyze the data. The results show that: 1) inclusive leadership could negatively influence on procrastination behavior; 2) mediating effect of intrinsic motivation was found between inclusive leadership and procrastination; 3) moderating effects of perceived insi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Based on this model, inclusive leaders demonstrate that they are individuals with unbiased judgments. They are leaders who manifest this behavior, learn, support, lead, and motivate their followers in reproducing IWB (Hantula, 2009;Lin, 2018). Inclusive leaders are more apt to show concern for followers' expectations and feelings, leading them to be more supportive of their subordinates (Javed et al, 2019).…”
Section: Inclusive Leadership Behaviorsmentioning
confidence: 99%
“…Based on this model, inclusive leaders demonstrate that they are individuals with unbiased judgments. They are leaders who manifest this behavior, learn, support, lead, and motivate their followers in reproducing IWB (Hantula, 2009;Lin, 2018). Inclusive leaders are more apt to show concern for followers' expectations and feelings, leading them to be more supportive of their subordinates (Javed et al, 2019).…”
Section: Inclusive Leadership Behaviorsmentioning
confidence: 99%
“…A study also showed that work characteristics link to workplace procrastination via individual processes of cognitive appraisal and self-regulation (Prem, Scheel, Weigelt, Hoffmann, & Korunka, 2018). Inclusive leadership also affect the employees procrastination in the workplace (Lin et al, 2018). Transformational leadership and organizational citizenship however related negatively with workplace procrastination (Metin, Peeters, & Taris, 2018).…”
Section: Literature Reviewmentioning
confidence: 98%
“…Support and interaction from leaders trigger an employee to be more passionate about the job, which lessens procrastination behavior. Employee behavior improves and leads to an excellent organizational image (Lin, 2018).…”
Section: Procrastinationmentioning
confidence: 99%